ETNOBOTANI SUKU TOGIAN DI PULAU MALENGE KECAMATAN TALATAKO, KABUPATEN TOJO UNA-UNA, SULAWESI TENGAH - Dalton Fidel Tabeo; Nurlina Ibrahim; Arsa Wahyu Nugrahani (Biocelebes, 2019)
Ethnobotany study in Togian Tribe has done in Tojo Una-Una, Central Sulawesi. This study was aimed to find out the information about the types of plants, used parts, processing, usage and dosage as well as knowing what type of disease treated using medicinal plants by Togian tribal communities in Malenge Island, Talatako District, Tojo Una- una, Central Sulawesi. This research  was a descriptive study with qualitative methods and used snowball sampling through interviews on four informants with the questionnaire. The results showed that 60 species are divided into 33 families. the most widely used was the Asteraceae by 7 species and Fabaceae familia by 6 species. Plant parts include leaves, stems, fruit, roots, rhizomes, herbs, seeds, sap and flowers partnered with the largest percentage of leaves 56%. the using and processing of medicinal plants by the Togian Tribe Malenge Island were boiled, mashed, squeezed, shredded, soaked, drunk, chewed, dropped, scrubbed, and pasted. the most  using and processing were boiled and drunk.